PENGARUH SUSU KEDELAI DOSIS 25 ml/kg BB TERHADAP BIOAVAILABILITAS TEOFILIN PADA TIKUS PUTIH JANTAN - Farida Hayati; Arief Rahman Hakim (Jurnal Ilmiah Farmasi, 2006)
Research has been conducted to study the effect of soya milk 25ml/kg BW per oral toward theophyline bioavailability when given concomittantly in male white rats. The study was done by using of wistar male white rats, weight 200-300 grams, age 3-4 month. The experimental design used was completely randomized design with two groups treatment, which each group test contained five rats. The first group (control) was given single dose pre-treatment of theophyline (25 ml/kg BW, orally), the second group (treatment) was given theophyline and soya milk (25 ml/kg BW, orally) with theophyline 25mg/kg BW. Blood samples were taken periodically from eye vein of rat in the 0,25; 1; 1,5; 3; 5; 6; 8; 10; and 24 hours. Determination of theophyline levels was done with HPLC by using Orcutt and friends method (1977) modified on the 269 nm wavelength. The concentration of theophyline was determined based on a standard curve. Theophyline bioavailability i.e. tmax, Cmax, and AUC0 inf was determined from the concentration to time data . Bioavailability parameters in the first group were tmax 2,36 ± 0,44 hours, Cmax 18,97± 2,06, AUC0 inf 231,48± 34,94 ug.hours/ml and bioavalibility parameters in the second group were tmax 2,08 ± 0,"l 7 hours, Cmax 24,11 ± 1,54, AUC0,nf 210,13±7,25 ug.hours/ml. The results indicated that soya milk was not found to be able to change theophyline bioavailability (P>0,05).